Effect of Resveratrol and Curcumin on Changes in Fatty Acid Composition and Oxidative Stress in Liver and Kidney Tissues of Rats Exposed to 7,12-Dimethylbenz[a]anthracene (DMBA) - Siltar, Yesim Bulut; Demir, Ersin; Erisir, Figen Erdem; Erdogdu, Ayse; Temizer, Ibrahim Akin; Yilmaz, Okkes (Pleiades Publishing Inc, 2024)
This study was conducted for the main purpose of evaluating the effect of resveratrol and curcumin on changes in fatty acid composition in liver and kidney tissues of rats exposed to DMBA. Resveratrol groups: 40 mg/kg resveratrol was administered for only 3 days per week throughout the experiment. Curcumin groups: 40 mg/kg curcumin was administered for only 3 days per week throughout the experiment. DMBA groups: A single dose of 20 mg/kg DMBA was administered once throughout the duration of the experiment. Fatty acid composition, fat-soluble vitamins, cholesterol and phytosterol analyses analyses were performed in tissues. Antioxidant tests were also performed. It was found that the amounts of C16:0, C17:0, C17:1 and C22:5 n3 decreased significantly in the liver tissue of rats administered DMBA, but the amounts of C20:3 n6 ve C22:6 n3 increased significantly. It was found that C16:0 and C18:2 n6c levels increased significantly in kidney tissue, but C17:1 level decreased significantly. As a result of the administration of Curcumin, Resveratrol, DMBA + Curcumin and DMBA + Resveratrol in both liver and kidney tissue, it was determined that some fatty acid values decreased significantly and some fatty acid values increased significantly. Compared to the DMBA group, it was determined that all groups studied had significant changes in the amount of some fat-soluble vitamins, cholesterol, sitosterols in tissues. In conclusion the administration of DMBA, resveratrol and curcumin both single and in combination, it was found that there may be significant changes in the fatty acid composition, fat-soluble vitamins, cholesterol and phytosterols in tissue.
Keywords: DMBA; resveratrol; curcumin; fatty acid composition; cholesterol; oxidative stress